Understanding the change and development of trust and the implications for new leaders - Dirks, Kurt T. (Journal of business ethics, 2022)
Leaders, particularly new leaders, seek to establish high levels of trust, as it has been associated with higher levels of effectiveness and group outcomes. This study is designed to understand how trust changes and develops for leaders in a new role and the implications of that change. Although calls for research on trust over time have been made for the past 2 decades, our knowledge of this phenomenon is still quite limited. The findings indicate that leader and unit performance is a function not only of absolute trust level, but is also affected by the direction and magnitude of change in trust across time periods, with the highest levels of effectiveness being associated with leaders who exhibited an increase in trust from the group over time. The data also suggest that the direction and rate at which trust grew was determined by initial expectations and transformational leadership behaviors.